NEEM PRODUCTS AGAINST COCONUT INSECT PESTS - S. Sadakathulla (International Coconut Community, 1993)
Three field experiments were conducted to find out the efficacy of neem products against the damage of rhinoceros beetle to coconut palm and termite damage to coconut palm and plaited leaves. The application of cither neem seed powder + sand (1:2) or neem seed kernel powder + sand (1:2) @ 150 g mixture per palm in the bases of three leaf axils in the crown, were found more effective against rhinoceros damage. Spraying of neem oil 5% or neem seed kernel extract 20% from the base and up to, 2 m height on the truck protected the palm from termites. Spraying with copper sulphate 1% and‑then neem oil 5% or copper sulphate 1% and then neem seed kernel extract 20% on plaited coconut leaves was found efficacious in protecting plaited coconut leaves for more than six months even when the plaited leaves were kept on the bare ground having persistent live termite colony throughout the year.